Validation of the Achalasia Patient‐Reported Outcomes Questionnaire. Issue 10 (20th September 2022) - Pandolfino, John E.; Carlson, Dustin A.; McGarva, Josie; Kahrilas, Peter J.; Vaezi, Michael; Katzka, David; Taft, Tiffany H.
Summary: Background: Achalasia is a debilitating major motor disorder of the oesophagus. Hypervigilance and symptom‐specific anxiety substantially impact dysphagia symptom reporting, and quality of life is a critical patient outcome. Earlier achalasia symptom scales did not consider these constructs in their psychometric development. Aim: To develop a new symptom measure, the Achalasia Patient‐Reported Outcomes (APRO) Questionnaire Methods: Four gastroenterologists with achalasia expertise generated preliminary items. Patients reviewed items via cognitive interviews. Patients undergoing high‐resolution manometry completed the APRO with Oesophageal Hypervigilance and Anxiety Scale, Northwestern Oesophageal Quality of Life Scale, and three measures of reflux and dysphagia. Full APRO psychometric assessment (reliability, validity, factor structure) was done. Cluster analysis evaluated APRO + symptom‐anxiety/hypervigilance patient phenotypes. Results: We included 961 patients with normal motility and 296 with achalasia. The APRO yielded three subscales: dysphagia, reflux, chest pain with two items for weight change and diet modifications. Reliability and validity were excellent. Twenty‐five percent of achalasia patients may have high levels of anxiety/hypervigilance despite low symptoms, while 8% may report severe symptoms with low anxiety/hypervigilance. The APRO significantly predicted quality of life, but less cognitive‐affective processes. Conclusions: The APRO is a reliable and valid measure of achalasia symptoms that addresses the limitations of existing questionnaires. Symptom anxiety and hypervigilance moderate the relationship between APRO and quality of life; 33% of patients with achalasia exhibit concerning patterns in symptom severity, anxiety and hypervigilance that may contribute to poorer outcomes. Abstract : The Achalasia Patient‐Reported Outcomes (APRO) scale was validated in 1257 patients undergoing high‐resolution manometry (296 achalasia, 961 normal motility). Symptom‐anxiety and hypervigilance, and quality of life were included in the APRO psychometric development. Patients may be phenotyped in one of four ways by how their symptoms align with hypervigilance and symptom anxiety to help guide clinical decision making and understand how quality of life may be affected.